Potential analysis of location, socio-culture and biodiversity as ecotourism attraction in Valentine Bay on Buano Island, West Seram, Maluku, Indonesia - Martha E. Siahaya; Paulus Matius; Marlon I Aipassa; Yaya Rayadin; Yosep Ruslim; HENDRIK S.E.S. APONNO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Siahaya ME, Matius P, Aipassa MI, Rayadin Y, Ruslim Y, Aponno HSES. 2021. Potential analysis of location, socio-culture and biodiversity as ecotourism attraction in Valentine Bay on Buano Island, West Seram, Maluku, Indonesia. Biodiversitas 22: 438-448. This study aims to analyze the potential of flora and fauna in the mangrove ecosystem as an attraction for ecotourism development, knowing the role of stakeholders in supporting ecotourism development strategies in the mangrove area of Valentine Bay in Buano island, West Seram, Maluku (Moluccas), Indonesia. Based on the results of the study, it was found that (i) The mangrove vegetation had 28 species of plants under 19 families. Vegetation at the level of seedlings, saplings, and trees was found, the dominant species being Rhizophora apiculata, Bruguiera gymnorrhiza, and Xylocarpus granatum. The diversity of animals in the Valentine Bay mangrove ecosystem consist of birds, insects, reptiles, mollusks, crustaceans, echinoderms, fish, and mammals. Furthermore, there was an endemic fauna of Buano island, namely the Kehicap buano/black-chinned monarch bird (Symposiachrus boanensis) which has started to become rare, and was declared as critically endangered (CR) by the International Union for Conservation of Nature and Natural Resources; (ii) Stakeholder involvement in ecotourism activities were very supportive; (iii) Development strategies were to develop ecotourism, promote ecotourism attractiveness, develop educational tourism and promote study on the diversity of flora, fauna, culture, and traditional customs on Buano island.